2021
DOI: 10.3390/nu13051688
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fatigue Effect of a Dietary Supplement from the Fermented By-Products of Taiwan Tilapia Aquatic Waste and Monostroma nitidum Oligosaccharide Complex

Abstract: The Taiwan Tilapia is an important aquaculture product in Taiwan. The aquatic by-products generated during Tilapia processing, such as fish bones and skin, are rich in minerals and protein. We aimed to explore the effect of a dietary supplement, comprising a mixture of fermented Tilapia by-products and Monostroma nitidum oligosaccharides as the raw materials, combined with physical training on exercise performance and fatigue. We used a mouse model that displays a phenotype of accelerated aging. Male senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Polysaccharides and their complexes are not only used as energy resources and building materials in organisms, but also exist in all cell membrane structures and participate in the activity of various cells. 14 Comparison of the results of forelimb grip strength, weight-bearing swimming and the rota-rod test may objectively reflect the differences in the endurance of mice among the experimental groups. 15 The results of the three tests showed that the anti-fatigue effect of Russian S. chinensis was better than that of the Chinese, which may verify the conclusion based on the polysaccharide composition detection, as described above.…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides and their complexes are not only used as energy resources and building materials in organisms, but also exist in all cell membrane structures and participate in the activity of various cells. 14 Comparison of the results of forelimb grip strength, weight-bearing swimming and the rota-rod test may objectively reflect the differences in the endurance of mice among the experimental groups. 15 The results of the three tests showed that the anti-fatigue effect of Russian S. chinensis was better than that of the Chinese, which may verify the conclusion based on the polysaccharide composition detection, as described above.…”
Section: Resultsmentioning
confidence: 99%
“…LG and MG, which act as a substrate source for glycolysis and energy production, are also key indicators of EEIF (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that oral administration of HWET significantly increased glycogen content in the liver, but only slightly enhanced that of muscle tissue (Figure 4). Chen et al [38] also indicated that a mixture of fermented tilapia by-products and Monostroma nitidum oligosaccharides significantly increased liver glycogen content and decreased BUN level post-exercise. It has been proposed that the re-synthesis of liver glycogen is the first priority when glucose is available after exercise, followed by the synthesis of muscle glycogen [39].…”
Section: Effects Of Hwet On Glycogen Levels In Liver and Muscle In Micementioning
confidence: 97%